Characterization of chemical short-range order in VCoNi medium-entropy alloy processed by spark plasma sintering. (1st July 2023) - Cai, Weijin; He, Junyang; Wang, Li; Yang, Wenchao; Xu, Xiangqi; Yaqoob, Khurram; Wang, Zhangwei; Song, Min
Abstract: Chemical short-range order (CSRO) in the VCoNi medium-entropy alloy (MEA) processed by spark plasma sintering (SPS) and hot-rolling (HR) is investigated in this study. Plenty of dislocations and stacking faults, along with nano-twins and V-oxide particles, are observed in the SPS-HRed MEA, leading to the sharp increase of strength compared to the cast counterpart with single FCC phase. Although the microstructures and associating thermal routes are fundamentally different from those in casting alloys, the CSRO in the SPS-HRed MEA shows the same L11 -type structure motif and very similar sub-nanometer size (0.71 nm). The preference of V-Co and avoidance of V-V pairs are seen, while the previously existing preference of V-Ni pair disappears due to the varying of matrix composition that relates to the processing techniques. This study thus offers valuable insights into the understanding of CSRO in the MEAs. Graphical abstract: Image, graphical abstract